Implementasi Mesin Roller Brush Pembersih Serbaguna Untuk Meningkatkan Kualitas dan Produktivitas di UMKM Bumbu LLR - Pangesthi, Lucia Tri; Prabowo, Prayudi Setiawan; Yunus; Ali Hasbi , Ali Hasbi; Saputra, Catur Surya; Prayogo, Aji Catur (Universitas Negeri Surabaya, 2025)
UMKM seasoning LLR is one of the UMKM that produces cooking spices. UMKM seasoning LLR is located in Putat village RT.05 / RW.01, Tanggulangin, Sidoarjo. Natural cooking spices produced by UMKM seasoning LLR made from selected natural spices consisting of shallots, garlic, various empon-empon tubers, and leaves. Based on observations made by the community service team in collaboration with students, it has been found that there are two problems, namely in the production and management aspects. In the production aspect, in particular, the process of cleaning raw materials includes the process of peeling and washing with tools only knives and ordinary washing tubs which take a very long time and a lot of labor. Problems in the management aspect are due to weak business management, especially in business bookkeeping and marketing management. Implementation of activities that include the preparation stage, implementation stage, monitoring and evaluation. The semi-automatic roller brush method multipurpose cleaning machine can increase production. The large capacity of the machine can speed up the process of washing materials and does not require a lot of labor. The machine has a capacity of 165 kg/hour. The machine is also equipped with a roller brush of seven plastic brush models so that it is elastic and also equipped with a spray model water hose to make it easier and able to remove dirt to difficult parts. The implementation of a multipurpose cleaning machine using the roller brush method can increase the speed of the washing process by about 15 times compared to the manual method. The washing results from the machine are also cleaner, more hygienic and the operation and maintenance of the machine is very easy. Management training using e-commerce and bookkeeping can increase knowledge to improve product.